2021
DOI: 10.1093/eurheartj/ehab772
|View full text |Cite|
|
Sign up to set email alerts
|

Role of plakophilin-2 expression on exercise-related progression of arrhythmogenic right ventricular cardiomyopathy: a translational study

Abstract: Aims Exercise increases arrhythmia risk and cardiomyopathy progression in arrhythmogenic right ventricular cardiomyopathy (ARVC) patients, but the mechanisms remain unknown. We investigated transcriptomic changes caused by endurance training in mice deficient in plakophilin-2 (PKP2cKO), a desmosomal protein important for intercalated disc formation, commonly mutated in ARVC and controls. Methods and results Exercise alone cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 29 publications
3
17
0
Order By: Relevance
“…This increase occurred despite the fact that desmin clusters, measured throughout the cell, were larger and more elongated in PKP2cKO cardiomyocytes than in controls and that desmin protein abundance was increased in PKP2cKO hearts (Figure S8B and S8C), as was also the case in hearts of patients with ARVC (Figure 3B). Consistent with data showing that altered nuclear morphology is a consequence of reduced desmin attachment, 22 we observed that nuclei of PKP2cKO myocytes were more circular than those of controls (Figure 4C).…”
Section: Dna Damage Occurs Independently Of a Significant Increase In...supporting
confidence: 92%
“…This increase occurred despite the fact that desmin clusters, measured throughout the cell, were larger and more elongated in PKP2cKO cardiomyocytes than in controls and that desmin protein abundance was increased in PKP2cKO hearts (Figure S8B and S8C), as was also the case in hearts of patients with ARVC (Figure 3B). Consistent with data showing that altered nuclear morphology is a consequence of reduced desmin attachment, 22 we observed that nuclei of PKP2cKO myocytes were more circular than those of controls (Figure 4C).…”
Section: Dna Damage Occurs Independently Of a Significant Increase In...supporting
confidence: 92%
“…In mice, plakophilin‐2 loss and training synergically worsened cardiac function because of a reduced reserve of desmosomal proteins. 72 Although in a limited sample, when adjusted for exercise, odds of proband status and ventricular arrhythmias did not differ between sexes, and, after introduction of exercise restrictions, disease progression did not differ between sexes. 69 …”
Section: Arrhythmogenic Cardiomyopathymentioning
confidence: 76%
“…A recent experimental model revealed that endurance training in PKP2 knockout mice decreased cardiac muscle mass and increased cardiac myocyte apoptosis, despite enhanced arrhythmogenicity such as increased fractional shortening and calcium transient amplitude. 9 Based on these findings, most ARVC patients with a PKP2 genetic variant might need to severely restrict daily exercise. The three siblings were heterozygous for the previously reported pathogenic splice site variation c.2489 + 1G > A in Intron 12 of the PKP2.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 8 Plakophilin-2 (PKP2) genetic variants has been shown to enhance progression of pathogenesis in ARVC in terms of systolic cardiac function and lethal arrhythmia. 9 A recent study using genetically PKP2 knockout mice showed that loss of the PKP2 function reduced ventricular systolic function and enhanced vulnerability to ventricular arrhythmia. The current study presents a case series of three siblings (sports athletes) with PKP2 genetic variants, where intensive training potentially promoted the pathogenesis of ARVC through early manifestation of ventricular tachyarrhythmia.…”
Section: Introductionmentioning
confidence: 99%